2019
DOI: 10.22214/ijraset.2019.1137
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Analysis of Heart Disease Using SVM Algorithm

Abstract: In this paper the proposed system predicts Heart Disease using SVM algorithm. Heart disease is the most common cause of death globally. Heart disease prediction using data mining is one of the most interesting and challenging tasks. The shortage of specialists and high wrongly diagnosed cases has necessitated the need to develop a fast and efficient detection system. According to past system the integration of clinical decision support with computer based patient record can reduce medical errors, can be made m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Finally, classifier performance has been evaluated. In the current research work, heart diseases have been identified based on the discussed process, depending on the historical dataset of patients and support vector machine classifier (Patil, 2019). The sequential steps followed for evaluation of the kernel parameters of the proposed prediction system have been presented in Fig.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Finally, classifier performance has been evaluated. In the current research work, heart diseases have been identified based on the discussed process, depending on the historical dataset of patients and support vector machine classifier (Patil, 2019). The sequential steps followed for evaluation of the kernel parameters of the proposed prediction system have been presented in Fig.…”
Section: Proposed Methodologymentioning
confidence: 99%